The Effect of Various Concentrations of Liquid Smoke with Time Differences on the Viability of Candida albicans - Nahla Nahla; Endang Sri Lestari; Nadia Hardini (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Dentures that are rarely cleaned will trigger the growth of Candida albicans, which is a fungus known to be a major cause of opportunistic infections of the oral cavity. Liquid smoke is a chemical produced by distillation of smoke from combustion, containing phenol, carbonyl and carboxylic acids that are effective in killing fungi.Objective: To determine the effect of various concentrations of liquid smoke with different periods of time on the viability of Candida albicans.Methods: This was an experimental laboratory research with post-test only control group design. This study used Candida albicans colonies as samples with 6 different treatment concentrations of liquid smoke (100%, 50%, 25%, 12.5%, and 6.25%) and different periods of time (5 and 15 minutes), with 5 duplications.Results: The Kruskal-Wallis test on the MIC (Minimum Inhibitory Concentration) showed that there are significant differences (p <0.001) in the experimental groups, while the test on the MBC (Minimum Bactericidal Concentration) also showed the same result (p <0.001). The Mann-Whitney test stated that there was a significant difference between liquid smoke concentrations of 12.5% with positive control. The lowest concentration that could inhibit the growth of Candida albicans is 12.5%. At 24 hours incubation with 5 and 15 minute soaking time, the MBC of Candida albicans was 100% with 15 minute soaking time.Conclusions: Liquid smoke affected the growth of Candida albicans, characterized by MIC at a concentration of 12.5% and MBC at a concentration of 100% with a 15-minute soaking time.